LITERATURE REVIEW: FAKTOR- FAKTOR PEMBERIAN MPASI DALAM KEJADIAN STUNTING - Mina Madinatuzzahrah; Isna Hudaya; Arum Meiranny (Bhamada: Jurnal Ilmu dan Teknologi Kesehatan (E-Journal), 2023)
Malnutrition is a significant problem in Indonesia. There are several conditions that affect the nutrition of children aged under five, namely stunting, low weight, and wasting. This condition occurs as a result of nutrition that is not in accordance with the life stages of the child. This condition is very influential for the health and survival of children in the long term. The purpose of this literature review study is to prove and study more deeply the use of KIA books in the provision of MPASI to prevent stunting. The method used in searching for the author's article uses the study literature review method, a search used using a database in the form of google scholar and pubmed, with the keywords "KIA Book", "complementary feeding", "Stunting". Articles obtained for review as many as 9 articles that fit the criteria, namely 6 national articles and 3 international articles. The results of MPASI giving factors that result in stunting are maternal factors in terms of education, knowledge (type of food given, frequency and amount of MPASI given), maternal KEK history, parenting, and social environment.